PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VII SMPN 3 RAMBAH HILIR PADA MATERI KLASIFIKASI BENDA TAHUN PEMBELAJARAN 2014/2015 - -, Hartati; Afifah, Nurul; Ade, Filza Yulina (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The purpose of this study is to know the influence of educational kooperatif type TGT model to result biology education for seven grade students SMPN 3 Rambah Hilir for object klasification. This research is as reseach an un real eksperiment, To take sampel with tecnic purposive sampling, This sampel the seven student grade class VIIA as the eksperiment and class VIIC as the instrument control. That using as the test.t. Result data count is deferent average both of the groups gets taccount = 3,50 with ttable =2,0066.for significant 5% (3,50 > 2,0066,) so we can conclude that any influence educational model cooperative TGT to result biology educational seven grade student SMPN 3 Rambah Hilir for topic object klasification the year 2014/2015.